Morphological and Molecular Identification of Stellantchasmus dermogenysi n. sp. (Digenea: Heterophyidae) in Thailand - Chalobol Wongsawad (2019)
We tried a series of morphological and molecular approaches to identify a new species of Stellantchasmus (Digenea: Heterophyidae) originating from the wrestling half-beaked fish, Dermogenys pusillus of Thailand. Adult worm samples of the new species were recovered from hamsters experimentally infected with the metacercariae from D. pusillus in Thailand. Two isolates (Thai and Korean) of Stellantchasmus falcatus were used as comparative control groups. Worm samples of 3 Stellantchasmus groups were morphologically observed and molecularly analyzed with the mitochondrial cytochrome c oxidase 1 gene. The morphological characteristics of S. dermogenysi n. sp. are similar to S. falcatus originating from brackish water fish, but minor difference was noted including the absence of the prepharynx, position of the ovary near the ceca end, smaller body size, and shorter esophageal length. A phylogenetic tree derived from neighborjoining and maximum-likelihood methods suggests that S. dermogenysi n. sp. is separated from S. falcatus supported by high bootstrap values. The relative divergences persist between these host-specific trematodes, which we suggest should be recognized as 2 distinct species. Comparisons of S. dermogenysi n. sp. with S. falcatus isolated from mullets in Thailand and Korea indicate a genetic divergence of mitochondrial DNA of 19.4% and 21.7%, respectively. By the present study, a new species, Stellantchasmus dermogenysi n. sp. (Digenea: Heterophyidae), is proposed in Thailand based on molecular evidences, in addition to minor morphological differences between S. falcatus and the new species.